ナンキョク ニオケル ウチュウ ブッシツ ニ カンスル ケンキュウ 3 インセキ ニツイテ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 島, 正子; シマ, マサコ; 岡田, 昭彦; オカダ, アキヒコ; 島, 誠; シマ, マコト; SHIMA, Masako; OKADA, Akihiko; SHIMA, Makoto (国立極地研究所, 1973)
P(論文) Antarctica is thought to be the most suitable place for searching extraterrestrial materials. Since 1965, we have been studying microtektite and cosmic dust in Antarctica. In 1969, the Japanese Expedition Team collected stony meteorites and brought them back to Japan. Scientific study of these samples has just been started. A part of the samples was examined for mineral composition, and was also analyzed for chemical composition by means of wet chemistry. At the same time, examination of rare gas was carried out with a gas mass-spectrometer. The purpose of the study is to know whether these meteorites are extraterrestrial materials or not. As a result, they were found to be chondrites, which are classified into enstatite chondrite, achondrite, carbonaceous chondrite and bronzite chondrite. For the samples we proposed the name Yamato (a), Yamato (b), Yamato (c) and Yamato (d), following Huss method. They were found on the glacier near the Yamato Mountains (70°S, 37°E) within a small area (about lOxlOkm^2). It is a quite interesting phenomena that different kinds of chondrites are found within a narrow area. This may indicate one shower of meteorites. Also, it is different kinds of chondrites fell at different times in a small area. Or the meteorites, which had fallen over a wide region, have been carried to this narrow area by the glacier movement. departmental bulletin paper